ANALISIS PENGARUH BI RATE, INFLASI, DAN INDEKS DOW JONES TERHADAP INDEKS HARGA SAHAM GABUNGAN - Rannisya Firdha Ibrahim; Medy Desma Fatwara (Unversitas Prof. Dr. Moestopo (Beragama), 2023)
Throughout 2017 to 2020, the sales performance of issuers in the pharmaceutical sub-sector has proven to record an increase. Referring to the results of observations made by researchers, it is known that pharmaceutical companies have experienced an increase, marked by the increasing number of pharmaceutical industries in Indonesia, where in the last 6 years (2015 – 2020), the domestic pharmaceutical industry has increased by 29 new companies, namely from a number of 198 industries in 2015 increased to 227 industries in 2020. The purpose of this study was to test and analyze Economic Value Added (EVA) on stock returns, Market Value Added (MVA) on stock returns and Economic Value Added (EVA) and Market Value Added (MVA) has a positive effect on stock returns. In this research method, manufacturing companies in the pharmaceutical sub-sector on the Indonesia Stock Exchange for the 2017-2020 period used a purposive sampling method and obtained a sample of 8 companies. The analytical method used is descriptive analysis, classical assumption test, multiple linear regression analysis, coefficient of determination, and correlation coefficient using SPSS version 25.0. The results of this study are that EVA has a positive and significant effect on stock returns, MVA has a positive and significant effect on stock returns. EVA and MVA simultaneously affect stock returns.